Eksistensi Hukum Internasional terhadap Hukum Nasional dalam Pembuatan Perjanjian Internasional - Halifa H; Mira Nila Kusuma Dewi; Sadikin S; Tri Andika; Andi Jihan; Anwar A (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The relationship between international law and national law is a fundamental issue in legal studies, particularly when states engage in international treaty-making. Indonesia, as a sovereign state, is bound by international obligations arising from treaty ratification, yet must at the same time uphold constitutional norms and principles of national law. This article analyzes the existence and applicability of international law within the Indonesian national legal system, focusing on theoretical approaches to the relationship between the two legal orders and practical implementation through ratification procedures under Law Number 24 of 2000 on International Treaties. The study indicates that Indonesia adopts a mixed approach, neither purely monist nor dualist, but situational according to national legal and political needs. Thus, the applicability of international law in Indonesia is not automatic but contingent upon formal approval by state authorities. This article offers a comprehensive understanding of how Indonesia balances its national legal sovereignty with obligations under international law.Â